“My happiness turned into sadness”: Intersectional analysis proposal on gender violence in the first dating relationships - Pérez Jiménez Fátima; Panadero Rosa Mogena (Temida, 2023)
Using the intersectional feminist proposal as a conceptual tool, this study analyses the experiences of young women who have suffered abuse from the beginning of the dating relationship and who have remained in the relationship for several years. The aim is to bring to light in a differentiated way the identities that converge in these young women and that, analyzed separately, favour a more elaborate and profound analysis of these experiences. The in-depth interviews have been the vehicle to get to know these experiences and the results show how being a woman, being young, and being a partner are identities that in a differentiated way are revealed as sustaining violence. Capturing these contrasts makes it possible to avoid a simplistic and generalizing analysis of all women victims, allowing for a more singular and specific understanding of this concrete reality.